Progress in lactic acid bacterial phage research - Mahony, Jennifer (BioMed Central, 2014)
Research on lactic acid bacteria (LAB) has advanced significantly over the past number of decades and these developments have been driven by the parallel advances in technologies such as genomics, bioinformatics, protein expression systems and structural biology, combined with the ever increasing commercial relevance of this group of microorganisms. Some of the more significant and impressive outputs have been in the domain of bacteriophage-host interactions which provides a prime example of the cutting-edge model systems represented by LAB research. Here, we present a retrospective overview of the key advances in LAB phage research including phage-host interactions and co-evolution. We describe how in many instances this knowledge can be pivotal in creating real improvements in the application of LAB cultures in commercial practice.